THYROXINE ABSORPTION TEST: A CASE SERIES OF PATIENTS WITH PERSISTENT PRIMARY HYPOTHYROIDISM - Lee, Xh; Nasruddin, Azraai; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Persistent primary hypothyroidism of any etiology despite high doses of levothyroxine replacement is a common encounter in our clinical practice. It is important to distinguish nonadherence (pseudo-malabsorption) from malabsorption. Thyroxine absorption test is required to make this distinction before further evaluations for malabsorption. We present our review on our institution’s experience with thyroxine absorption test and evaluate its role and clinical impact on management of persistent primary hypothyroidism. RESULTS All 5 patients tolerated the absorption test well and showed >100% rise in Free T4 level at the fourth hour. During subsequent visits, 4 out of 5 patients were able to achieve normal thyroid function with the same, if not, a lower dose of levothyroxine. Two patients continued to show fluctuations in TSH trend during follow-ups. There were discrepancies in the test protocol on levothyroxine dosage and sampling time. CONCLUSION Thyroxine absorption test is a useful tool to distinguish between nonadherence and malabsorption. It negates unnecessary extensive search for causes of malabsorption. It provides objective information to guide discussions between clinicians and patients in addressing the issue of nonadherence.